Mission: Impossible? On empirical-normative collaboration in ethical reasoning - Schleidgen, Sebastian; Jungert, Michael; Bauer, Robert (Ethical Theory and Moral Practice, 2010)
During the 1980s, empirical social sciences and normative theory seemingly converged within ethical debates. This tendency kindled new debates about the limits and possibilities of empirical-normative collaboration. The article asks for adequate ways of collaboration by taking a closer look at the philosophy of science of empirical social sciences as well as normative theory development and its logical groundings. As a result, three possible modes of cooperation are characterized: first, the empirical assessment of conditions that actually necessitate the translation of normatively derived basic principles into practice rules; second, the empirical assessment of conditions for application of a moral norm which are formulated by bridging principles; third, the empirical assessment of social practice which allows (a) to measure whether adopted norms actually are implemented in practice or not and (b) to encounter new moral problems which are in need of ethical guidance. Finally, the article defends a symbiotic position in Weaver's and Trevino's triad of possible approaches to empirical-normative collaboration in ethics. © 2009 Springer Science+Business Media B.V.
Keywords: Ethik und Empirie; naturalistischer Fehlschluß; Sein-Sollen-Dichotomie; empirical ethics; naturalistic fallacy; empirical-normative collaboration; Hume's Law